Short Communication: Identification of Mildew Locus O (MLO) genes in Durio zibethinus genome corresponding with the Powdery Mildew disease - RAHMAT AZHARI KEMAL; ERIC BERNARDUS L. SANDJAJA; AUDI PUTRA SANTOSA; JEREMIAS IVAN (Biodiversitas Journal of Biological Diversity, 2018)
Kemal RA, Sandjaja EBL, Santosa AP, Ivan J. 2018. Short Communication: Identification of Mildew Locus O (MLO) genes in Durio zibethinus genome corresponding with the Powdery Mildew disease. Biodiversitas 19: 2204-2212. Mildew Locus O (MLO) is a protein consisting of seven transmembrane domains and appears in the various type of plants. MLO proteins are classified into seven clades. It is known that specific clades have different roles in a plant. MLOs from Clades IV and V have been linked to plant's susceptibility to Powdery Mildew (PM) disease. This study aimed to provide an overview of MLO genes present in durian (Durio zibethinus) genome. Bioinformatic analyses were conducted to analyze the phylogeny and structure of MLO genes and proteins in durian. The result showed that there were 20 putative DzMLO genes in durian, encoding 39 putative DzMLO proteins. Durian MLOs belong to Clade I-VI with one protein belongs to Clade IV and five proteins belong to Clade V. Those six MLO proteins shared a common motif in C-terminal and second intracellular domains. Putative alternative splicing and differential expressions were observed among Clade V DzMLO genes. These findings will facilitate the functional characterization of MLO genes and proteins in durian. Functional studies, especially on C-terminal and second intracellular domains, need to be conducted to elucidate the role of MLO in PM susceptibility in durian.